Increasing Adoption and Varietal Turnover of Seed—Consumer and Producer Side Interventions - Van Campenhout, Bjorn (International Food Policy Research Institute, 2023)
This presentation was given at LICOS KULeuven (Belgium) on Monday, June 19, 2023.